Mass Spectrometry investigation of 17α-Ethinylestradiol and Drospirenone complete removal from synthetic wastewater using Ozonation - Phellipe H. Amarala & b, Daniel M. Oliveirac, Alexandre Romaninic, Elias P. Tessaroa & b, Jose E. Padilhad, Deleon N. Correaa, Nelci F. Hoehra, Marcos N. Eberlina, Giovana A Batagliona, Eduardo C. Meurerd (Journal of Applied Pharmaceutical Science, 2017)
17α-ethinylestradiol (EE2) and drospirenone (DRO) are steroidal birth control compounds of widespread use and the presence of these two compounds in effluents and drink water have been related with a variety of diseases such as cancer and metabolic changes in humans. This paper describes the use of FT-ICR-MS and HPLC-MS/MS to investigate the removal of EE2 and DRO from synthetic wastewater simulating an industrial pilot plant residue, using an ozone treatment pilot plant. Ab initio calculations have been also performed suggesting that the lower energy pathway for drug degradation involves the action of singlet oxygen to these steroidal species. Total elimination of EE2 and DRO were achieved after 3 and 28 min, respectively. Estrogens degradations were screened via FT-ICR MS analyses in both positive and negative ion modes, and no residual organic molecules could be detected showing extensive oxidation and near total conversion to small volatiles or inorganic material.
Keywords: Mass Spectrometry, 17&alpha; -ethinylestradiol, Drosperinone, Ozonation.